Spear Brata: Pamor Spear and Tinatah Inspired Motif Teachings of Hastabrata - Intan Anggun Pangestu; Karju (East Asian Journal of Multidisciplinary Research, 2022)
The creation of the work with the title "Spear Brata: Pamor Spear and Motif Tinatah Inspired Hastabrata Teachings". This creation focuses on the shape of dhapur and tinatah motif on the spear blade whose motif is inspired by the symbol of natural elements in the teachings of Hastabrata. Hastabrata is the eight promises (brata) of a true leader who possesses eight symbols of the universe as a harmonization. This symbol consists of the sky, sun, wind, stars, water, fire, earth, and moon. The symbol used as the inspiration for the creation of this spear there are five elements of nature, namely land, water, stars, sun, and fire. The purpose of this creation is to: 1) Explaining the concept of spear creation with a tinatah motif, 2) Explaining the steps of spear creation with pamor. 3) Visualization of the shape of the spear work, presentation design and publication. The concept of spear creation uses the concept of vehicle transfer, reinterpretation of sanggit, and revitalization of sanggit. This method of spear creation is exploration, design, and embodiment.